Emerging RNA-centric technologies to probe RNA-protein interactions: importance in decoding the life cycle of positive sense single strand RNA viruses and antiviral discovery - Ghosh, Sreemoyee; Kumar, Shivam; Verma, Rohit; Ansari, Shabnam; Chatterjee, Samrat; Surjit, Milan (Frontiers in Cellular and Infection Microbiology, 2025)
Positive sense single strand RNA (+ssRNA) viruses are one of the evolutionary successful organisms and many of them pose a significant threat to human health. Diseases caused by +ssRNA viruses such as COVID-19, Flu and acute viral hepatitis are major public health concern worldwide. Therefore, a lot of research is focused at decoding the life cycle of +ssRNA viruses and develop specific antiviral therapeutics against them. Interaction of the viral RNA with virus-encoded proteins and host proteins drives the lifecycle and pathogenesis of +ssRNA viruses. Recent developments in computational and high-throughput omics-based experimental technologies offer the sensitivity and specificity for molecular characterization of these RNA-protein complexes. These are promising tools to revolutionize the field of +ssRNA virus research and pave the way for antiviral discovery. This review summarizes the current scientific resources available to characterize the RNA-protein interactome of +ssRNA viruses and provides an overview of the drug discovery pipeline for developing antivirals against pathogenic +ssRNA viruses.